Electrocardiographic criteria for localization of ventricular premature complexes from the inferior right ventricular outflow tract - Li, Kang; Lv, Pinchao; Wang, Yuchuan; Fan, Fangfang; Ding, Yansheng; Li, Jianping; Zhou, Jing (Frontiers in Cardiovascular Medicine, 2022)
BACKGROUND: The ventricular premature complexes (PVCs) originating from the superior right ventricular outflow tract (RVOT) have high success rates by catheter ablation. It may not be the same when the origin is in the inferior RVOT. OBJECTIVE: To identify electrocardiographic (ECG) characteristics that predict the site for successful ablation of PVCs originating in the inferior RVOT. METHODS: Of 309 consecutive patients with symptomatic PVCs despite medical therapy, 124 had PVCs originating from the RVOT, and 107 RVOT cases without structural heart disease and no bundle branch block in sinus rhythm were enrolled in the study. Among them, 74 have a superior RVOT origin, and 33 have an inferior RVOT origin. RESULTS: The proportion with multiple morphologies of PVC was significantly higher in the inferior RVOT group than in the superior RVOT group (24.24% vs. 6.76%, P=0.011). The QRS duration of PVCs with an inferior RVOT origin was more expansive than PVCs with a superior RVOT origin (162.42 ± 19.69 ms vs. 140.90 ± 11.30 ms; P<0.001). Furthermore, the QRS wave in V1 in patients in the inferior RVOT group was more likely to have a negative delta wave at the onset of the QRS (27.27% vs. 1.39%, P<0.001). We found that the areas under the receiver-operating characteristic curve (AUCs) for PVC diagnosis with an inferior RVOT origin ranged from 0.812 to 0.841 depending on ECG features, with the highest AUC for the QRS duration of PVCs and the amplitude of R waves in lead II. These ECG indices had good predictability for judging the origin of PVCs in the RVOT; the best threshold for the QRS duration of PVCs was 145 ms, and the best thresholds for the amplitude of R waves in leads II, III, and aVF were 1.35 mV, 1.35 mV, and 1.15 mV, respectively. CONCLUSION: When evaluating a patient with PVCs, the source is likely to be the inferior RVOT if the ECG presentation conforms to the morphological characteristics of the RVOT, meanwhile, the QRS wave is relatively broad and polymorphic, and the main waves in limb leads (II, III, and aVF) are upward with low amplitude.